\(x^2\left(x^2+4\right)-x^2+4=x^4+4x^2-x^2+4=x^4+3x^2+4\)
\(=\left(x^4+4x^2+4\right)-x^2\)
\(=\left(x^2+2\right)^2-x^2\)
\(=\left(x^2+x+2\right)\left(x^2-x+2\right)\)
\(x^2\left(x^2+4\right)-x^2+4=x^4+4x^2-x^2+4=x^4+3x^2+4\)
\(=\left(x^4+4x^2+4\right)-x^2\)
\(=\left(x^2+2\right)^2-x^2\)
\(=\left(x^2+x+2\right)\left(x^2-x+2\right)\)
phân tích đa thức thành nhân tử \(x^2\cdot\left(x+4\right)^2-\left(x+4\right)^2-\left(x^2-1\right)\)
Phân tích đa thức thành nhân tử
a)\(x\cdot\left(x+1\right)\cdot\left(x+2\right)\cdot\left(x+3\right)+1\)
b)\(\left(x^2-x+2\right)^2+4\cdot x^2-4\cdot x-4\)
c)\(\left(x+2\right)\cdot\left(x+4\right)\cdot\left(x+6\right)\cdot\left(x+8\right)+16\)
phân tích đa thức thành nhân tử
\(9\cdot\left(x^4+x^2+1\right)-\left(x^2+x+1\right)^2\)
Phân tích các đa thức sau thành nhân tử:
\(\left(5x-4\right)\cdot\left(4x-5\right)+\left(5x-1\right)\cdot\left(x+4\right)+3\cdot\left(3x-2\right)\)
\(\left(5x-4\right)^2+\left(16-25x^2\right)+\left(5x-4\right)\cdot\left(3x+2\right)\)
\(\left(x^2+3x+1\right)\cdot\left(x^2+3x+2\right)-6\)
phân tích đa thức sau thành nhân tử
Phân tích đa thức thành nhân tử: \(\left(x+5\right)^2+4\left(x+5\right)\left(x-5\right)+4\left(x^2-10x+25\right)=0\)
Phân tích các đa thức sau thành nhân tử:
\(x^2\left(x+4\right)^2-\left(x+4\right)^2-\left(x^2-1\right)\)
Phân tích đa thức thành nhân tử:
a) \(\left(xy\right)^2-xy-2\)
b) \(x^4-8x^3-16x^2+2\left(x^2-4x+4\right)-43\)
phân tích đa thức thành nhân tử
\(x^2-\left(m+n\right)x+m\cdot n\)